PROMOTION MIX MANAGEMENT AT MAHAR AGUNG WEDDING ORGANIZER: PROMOTION MIX MANAGEMENT AT MAHAR AGUNG WEDDING ORGANIZER - Aqobah, Dinda Adelia; Dewi, S.Sos., M.Med.Kom., Putri Aisyiyah Rachma (The Commercium, 2023)
This is a descriptive research with a qualitative approach titled "Management of Promotion Mix at Mahar Agung Wedding Organizer." The objective of this research is to explore how Mahar Agung Wedding Organizer manages the promotion mix in overall marketing communication. The research method used is descriptive qualitative. The findings of the research indicate that Mahar Agung Wedding Organizer employs several strategies in managing the promotion mix. In terms of advertising, they utilize advertising media such as Instagram and also print media such as brochures distributed during exhibitions. Their personal selling strategy is actively involved in exhibition events and weddings. For sales promotion, Mahar Agung offers special deals, discounts, wedding packages, collaborations with reputable vendors, and efforts to strengthen their brand image. In terms of direct marketing, they utilize the company’s database to review previous customer records and offer their services at special prices. Additionally, they engage in public relations promotions through exhibitions and participation in events organized by vendors. Keyword: Promotion Mix, Mahar Agung, Wedding Organizer